2017
DOI: 10.1017/s0033291717000113
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deep brain stimulation of the ventral anterior limb of the internal capsule on cognition in depression

Abstract: vALIC DBS neither has a lasting positive nor negative impact on cognition in TRD patients. DBS surgery might have a temporary negative effect on verbal memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…88 No permanent impact (either positive or negative) on cognition was observed in a posterior study with the same sample. 89 A double-blind crossover trial with seven TRD patients investigated the stimulation in either the anterior limb of the internal capsule/BNST or in the ITP. All of the patients participated in the follow-ups for at least 3 years, but some were followed-up up to 8 years after the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…88 No permanent impact (either positive or negative) on cognition was observed in a posterior study with the same sample. 89 A double-blind crossover trial with seven TRD patients investigated the stimulation in either the anterior limb of the internal capsule/BNST or in the ITP. All of the patients participated in the follow-ups for at least 3 years, but some were followed-up up to 8 years after the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…While open label studies of VC/VS demonstrated promising results (39), a previous randomized-controlled RECLAIM study on the subject was halted early due to lack of significant difference between the two arms after 30 patients had been enrolled (40). Interestingly, in a RCT of 25 patients with bilateral VC/VS DBS in the Netherlands, discontinuation of therapy during the crossover phase resulted in reemergence of symptoms (41). Fifty percent response and 30% remission was noted in open-label longterm follow-up of 28 patients receiving subcallosal cingulate stimulation (42).…”
Section: Depressionmentioning
confidence: 99%
“…DBS has been widely used, particularly for Parkinson’s disease, for over 30 years. Increasingly over the last decade, DBS has been applied to the treatment of psychiatric disorders including treatment-resistant depression ( 14 17 ), obsessive compulsive disorder (OCD) ( 18 , 19 ) and addictions ( 20 ). The US Food and Drug Administration approved a humanitarian device exemption for DBS in the treatment of severe OCD in 2009.…”
Section: Introductionmentioning
confidence: 99%